Shakedown of composite frames taking into account plastic and brittle fracture of elements = Przystosowanie ram zespolonych z uwzględnieniem plastycznego i kruchego zniszczenia elementów - Alawdin, Piotr; Bulanov, George (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper the mathematical model of the optimization problem of limit and shakedown analysis for composite plane frames, containing elastic-plastic and brittle elements under low-cyclic loading, is proposed. It is assumed that the load varies randomly within the specified domain, and limited plastic redistribution of forces in such structures occurs. An example of the shakedown analyses of the composite frame is given.
Keywords: ramy zespolone; ramy stalowo-betonowe; elementy sprężysto-plastyczne; zniszczenie elementów; optymalizacja nośności granicznej; model matematyczny; composite frame; steel-and-concrete frame; elastic-plastic elements; destruction of elements; limit load optimization; mathematical model